High climate model dependency of Pliocene Antarctic ice-sheet predictions - Aisling M. Dolan (Nature Portfolio, 2018)
Ice sheet models forced by climate model output indicate ice-sheet retreat during the Pliocene, yet concerns remain regarding potential model bias. Here, the authors present results from the Pliocene Ice-sheet Modelling Intercomparison Project, and show that results are highly dependent on the model forcing used.